International bulletin of the International secretariat of glass- workers / . Information of the International secretariat of glass-workers
Continued by: Bulletin international of the Federation of the Glass workers (ZK 16012). German ed.: Mitteilungen des Internationalen Sekratariats der Glasarbeiter (ZO 16123). - French ed.: Bulletin (international) du secrétariat international des ouvriers du verre (ZO 16123). - Also titled: Information of the International secretariat of glass-workers.